The Present and Future of Novel Protein Degradation Technology - Xia, Liwen; Liu, Wei; Song, Yinsen; Zhu, Hailiang; Duan, Yongtao (Current Topics in Medicinal Chemistry, 2019)
Proteolysis targeting chimeras (PROTACs), as a novel therapeutic modality, play a vital role in drug discovery. Each PROTAC contains three key parts; a protein-of-interest (POI) ligand, a E3 ligase ligand, and a linker. These bifunctional molecules could mediate the degradation of POIs by hijacking the activity of E3 ubiquitin ligases for POI ubiquitination and subsequent degradation via the ubiquitin proteasome system (UPS). With several advantages over other therapeutic strategies, PROTACs have set off a new upsurge of drug discovery in recent years. ENDTAC, as the development of PROTACs technology, is now receiving more attention. In this review, we aim to summarize the rapid progress from 2018 to 2019 in protein degradation and analyze the challenges and future direction that need to be addressed in order to efficiently develop potent protein degradation technology.
Keywords: progress